Orbital degeneracy removed by charge order in triangular antiferromagnet AgNiO2. - Wawrzyńska, E; Coldea, R; Wheeler, E; Mazin, I; Johannes, MD; Sörgel, T; Jansen, M; Ibberson, R; Radaelli, P (2007)
We report a high-resolution neutron diffraction study on the orbitally degenerate spin-1/2 hexagonal metallic antiferromagnet AgNiO2. A structural transition to a tripled unit cell with expanded and contracted NiO6 octahedra indicates sqrt[3]xsqrt[3] charge order on the Ni triangular lattice. This suggests charge order as a possible mechanism of lifting the orbital degeneracy in the presence of charge fluctuations, as an alternative to the more usual Jahn-Teller distortions. A novel magnetic ground state is observed at low temperatures with the electron-rich S=1 Ni sites arranged in alternating ferromagnetic rows on a triangular lattice, surrounded by a honeycomb network of nonmagnetic and metallic Ni ions. We also report first-principles band-structure calculations that explain microscopically the origin of these phenomena.